Microfinance Institution Services and Performance of Small and Medium Enterprises in Kabale District Uganda - Agaba, Agaba Moses; Mugarura, Elijah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2023)
This study evaluated the performance of small and medium businesses in Kabale District in relation to microfinance institution services. The precise goals were to determine how financial literacy education, managerial skill development, and marketing assistance provided through SME clubs and marketing associations affected the performance of small and medium-sized businesses. The study was descriptive in nature, and the data collecting and analysis methods used were quantitative. A questionnaire was used to collect data from a sample of 71 different SME owners and other relevant informants. Microsoft EXCEL and SPSS Version 22.0 were used to analyze the data and produce both descriptive and inferential statistics. The study concluded. Savings literacy, debt literacy, and investment literacy programs helped business owners safely manage their income, expenses, and savings, make clear financial decisions, repay loans on time, and diversify their investments, all of which boosted the performance of SMEs. By enhancing SME governance, boosting business vision through achieved goals and plans, and inspiring employees to work hard for better, the development of managerial skills positively impacted the performance of small and medium-sized enterprises. This ensured SMEs' capacity to compete, survive, and thrive in a dynamic environment. The study further supported the idea that SMEs performed better when marketing was facilitated through SME clubs and marketing groups.